FEATURES OF TRANSLATING TABOOS AND EUPHEMISMS FROM GERMAN INTO RUSSIAN - Zainabkhon Gazieva (International Journal of Literature and Language Studies, 2026)
The translation of taboos and euphemisms is one of the most challenging areas of intercultural communication and translation studies. Taboos and euphemisms reflect the cultural, social, and linguistic characteristics of a particular society. When translating from German into Russian, translators often encounter difficulties caused by differences in cultural norms, social values, and linguistic traditions. This article examines the specific features of translating German taboos and euphemisms into Russian, identifies the main translation strategies, and analyzes examples from different semantic fields.